Two approximate algorithms for model counting - Wang, Jinyan; Yin, Minghao; Wu, Jingli (Theoretical computer science, 2017)
Model counting is the problem of computing the number of models or satisfying assignments for a given propositional formula, and is #P-complete. Owing to its inherent complexity, approximate model counting is an alternative in practice. Model counting using the extension rule is an exact method, and is considered as an alternative to resolution-based methods for model counting. Based on the exact method, we propose two approximate model counting algorithms, and prove the time complexity of the algorithms. Experimental results show that they have good performance in the accuracy and efficiency.